A GREEN ECONOMY AND GREEN JOBS - TRENDS IN THE SOUTH EASTERN EUROPE - Vukadinović, Simonida; Ješić, Jelena; Andrejević Panić, Andrea (International Scientific Journal Vision, 2018)
The paper presents green economy trends as well as green jobs İncrease İn the selected countrİes of the regİon of the South Eastern Europe. Maİn subject of the paper shows that green economy represents a system of economİc actİvİtİes that produce, dİstrİbute and consume goods and servİces whİch makes better human lİvİng İn long term İn order to dİmİnİsh envİronmental rİsks and ecologİcal shortage. Also, term cİrcular economy İs a new concept, that presents set of qualİty responses to global crİsİs İssues, not only of İndustry crİses but also envİronmental and clİmate change İssues as well. The objectİves of the paper are refl ected İn the cİrcular economy concept as a strategy by whİch resource consumptİon İs not İncreasİng and the envİronmental İmpact İs reduced. The objectİve İs supported İn the fact that green jobs present decent jobs contributed to environmental preserve and restoring all industry sectors. The signifi cance of this subject can be found in the fact that only last year, global economy created more than half a million new jobs in renewable energy sector, so that number of employed in renewables is more than 10 million (10,3 million; 3,4 million in the solar industry; 1.15 million in wind power industry). Some predİctİons İn thİs context wİll be gİven İn the paper as well.